Bending the aging curve the complete exercise guide for older adults - Signorile, Joseph F. (Human Kinetics, 2011)
Bending the Aging Curve provides fitness professionals with a multifaceted periodized training program specifically for older adults. With this book and DVD package, you will find the tools you need to help your clients slow the physical decline that can accompany aging. This one-of-a-kind resource presents a scientifically substantiated and practically proven training system that can extend the vitality of our aging population. Dr. Signorile offers an engaging explanation of the research behind his exercise diagnosis and prescription model while maintaining a focus on the practical components of program design. You will learn to use tests to diagnose your clients' needs and then prescribe training cycles with the appropriate mix of work, active recovery, and skill practice to maximize functional improvements.--[book cover]